2022
DOI: 10.3390/life12122125
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Some New Drugs and Prevalence of ESBL- and MBL-Producing Enterobacteriaceae Uropathogens Isolated from Diabetic Patients

Abstract: Diabetes is a leading non-communicable disease and a risk factor for relapsing infections. The current study was aimed at investigating the prevalence and antibiotic susceptibility of carbapenem-resistant (CR) uropathogens of the family Enterobacteriaceae in diabetic patients. The data of 910 bacterial isolates was collected from diagnostic laboratories during January 2018 to December 2018. The bacterial isolates were identified using traditional methods including colonial characteristics, biochemical tests, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
2
1
1
Order By: Relevance
“…The resistance patterns of both groups (ward and OPD) of the isolates showed higher resistance to penicillin, cephalosporins, and quinolones. This is consistent with the results of a previous study [25].…”
Section: Discussionsupporting
confidence: 94%
“…The resistance patterns of both groups (ward and OPD) of the isolates showed higher resistance to penicillin, cephalosporins, and quinolones. This is consistent with the results of a previous study [25].…”
Section: Discussionsupporting
confidence: 94%
“…Carbapenemase are another important group of βlactamases, belonging to different ambler classes (A, B, D) can hydrolyze broad range of βlactams including penicillin, cephalosporin, aztreonam and carbapenem. The present findings were correlated with the previous study reports that 127/142 (89.4%) UPEC isolates were carbapenemase producers by phenotypic method [38] and the prevalence of 31.3% (36/115) UPEC were metallo β-Lactamase by Modified Hodge Test [39].…”
Section: Discussionsupporting
confidence: 92%
“…(TEM), Sulfhydryl Variable (SHV) and Cefotaximase (CTX-M). Prevalence of ESBL coding genes among diabetic isolates in the present investigation were higher than one of the similar study reports that 58.2% of phenotypically ESBL producers among these 26.6% harbor blaTEM and 12.5% harbor blaCTX-M among diabetic UPEC [38]. ESBL production in Type 2 diabetic UPEC (25.8%) were positively correlated with old age, urinary catheterization, discriminate use of antibiotics and acute kidney injury [24].…”
Section: Discussioncontrasting
confidence: 53%
“…These species are considered the most commonly isolated around the world, both in community and hospital settings. Some studies conducted in Germany, Espana, Peruvia, Ethiopia, Tanzania, and Ghana highlighted the same constatation (Abubaker and Anwar, 2023;Alzahrani et al, 2022;Donkor et al, 2019;Moges et al, 2021;Rondon et al, 2023;Schmider et al, 2022;Stoltidis-Claus et al, 2023). However, this pattern may vary in certain areas, as seen in a study conducted in Sierra Leone, where samples from the community showed a predominance of Citrobacter freundii strains (Leski et al, 2016) and another study among elderly patients living in the community and in the nursing home showed that Proteus mirabilis was the second strains isolated after E. coli (Pulcini et al, 2019).…”
Section: Discussionmentioning
confidence: 86%